2018
DOI: 10.1111/vsu.12796
|View full text |Cite
|
Sign up to set email alerts
|

Protocol changes to reduce implant‐associated infection rate after tibial plateau leveling osteotomy: 703 dogs, 811 TPLO (2006‐2014)

Abstract: The protocol reported here may be used as a guide in clinics seeking to reduce their IAI rates after TPLO. Postoperative infections after implementation of this protocol should be monitored to evaluate its potential impact on the emergence of antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…When these concerns are combined with the previously discussed data that provide evidence that protocol changes in perioperative and postoperative animal care drastically diminished infection rates in TPLO surgeries without changing antibiotic regimens, it may be easier to argue that antibiotics used postoperatively in TPLO surgeries are not warranted. 14 Regardless of one's disposition on this issue, additional research is crucial to aid clinicians in clinical decision making and should address these concerns. This research must include a set of standardized treatment guidelines for each group in a study and should include culture and sensitivity results as part of the definition of an SSI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When these concerns are combined with the previously discussed data that provide evidence that protocol changes in perioperative and postoperative animal care drastically diminished infection rates in TPLO surgeries without changing antibiotic regimens, it may be easier to argue that antibiotics used postoperatively in TPLO surgeries are not warranted. 14 Regardless of one's disposition on this issue, additional research is crucial to aid clinicians in clinical decision making and should address these concerns. This research must include a set of standardized treatment guidelines for each group in a study and should include culture and sensitivity results as part of the definition of an SSI.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, authors of a recent article found that the changes in perioperative and postoperative protocols altered infection rates in TPLO surgeries without changing antibiotic regimens. 14 Furthermore, the determination of infection varied throughout the studies and may, in part, be responsible for the wide range of infection rates noted. Most studies used a broad category of subjective clinical signs, with limited emphasis or requirement for objective culture evaluation to confirm infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study in dogs outlined an aseptic TPLO protocol that led to a significant decrease in post‐TPLO infection rate and implant removal . From the value‐based point of view, the lower incidence of complications improved the value (better outcomes and lower costs) provided to dogs that benefited from the aseptic protocol.…”
Section: Learning Toolmentioning
confidence: 99%